E-pedagogy and e-assessment - Bobby Elliott (2008)
Teaching practice has changed little during the last century. It is argued that the classical pedagogies are timeless and not subject to the whims of technological change. The proponents of change argue that the learning environment has fundamentally changed and that pedagogy must evolve to reflect this new reality. This paper explores this argument and examines what, if any, are the implications of an “e-pedagogy” for assessment.